SURAT AL-AHZAB AYAT 21 SEBAGAI METODE KETELADANAN PENDIDIKAN - Lathifatul Khasanah (JIEBAR : Journal of Islamic Education: Basic and Applied Research, 2023)
The value of education in Surat Al-Ahzab becomes an example for mankind who discusses the Prophet Muhammad as a person who is an example in everyday life. This research uses a literature review that discusses Surah Al-Ahzab verse 21 and is analyzed with related sources related to the discussion. The results obtained in this study are Surah Al-Ahzab Verse 21 is one of the verses that is rich in Islamic teachings about tolerance and justice. In the context of Islamic education, this verse can be used as a strong exemplary method to shape character and morals. By understanding the meaning, context, and values contained in this verse, Islamic educators can guide the younger generation of Muslims in better understanding and applying the teachings of Islam. Through the application of exemplary methods by referring to the example of the Prophet SAW, we can form better, tolerant, and just individuals in society. Hopefully this article has provided a deep insight into the role of Verse 21 in Islamic education.